PENERIMAAN MAHASISWA BARU BERBASIS WEBSITE PADA UNIVERSITAS KARYADARMA KUPANG - Maria, Dina; Henuk, Hildayanti (STIKOM Uyelindo Kupang, 2020)
New Student Admission Information System at Karyadarma University has not used a web-based information system. This information system is an information system used to facilitate the registration administration process so as to make it easier for the Admissions Committee at the University of Kupang Karyadarma. In developing the New Student Admission Information System using the Laravel framework method. This information system uses the PHP programming language and MYSQL database server. The system testing method uses blackbox and usability testing. The results of this study are a website-based New Student Admission Information System that can help the ongoing performance. The results of testing the software that was developed obtained a functionality value of 1 (Good), testing the usability aspect obtained results with a percentage of 94.66% (Very Eligible).